Apoptotic Responses Mediated by Nostoc-Synthesized Silver Nanoparticles against Ehrlich Ascites Carcinoma Tumor-Bearing Mice. (16th January 2023) - Hamida, Reham Samir; Albasher, Gadah; Bin-Meferij, Mashael Mohammed
Abstract : Among the metallic nanoparticles (NPs), silver NPs are the leading anticancer nanoagents due to their physicochemical properties and inhibitory activities against different cancers. Many reports exhibited the cytotoxic effect of silver-NPs fabricated by cyanobacteria against various cancer cell lines. However, their lethal mechanisms have not been elucidated. The antiproliferative and cytotoxic effects of silver-NPs synthesized previously using Nostoc Bahar M (N-SNPs), and their associated mechanisms were evaluated in the solid Ehrlich ascites carcinoma (EAC) tumor-bearing mice model. Blood parameters, liver enzymes (alanine transaminase, aspartate aminotransferase, and alkaline phosphatase), lactate dehydrogenase, adenosine triphosphate, and oxidative stress markers, including glutathione, glutathione peroxidase, catalase, and malondialdehyde, were analyzed. In addition, the expression of pro- and antiapoptotic genes and proteins was screened utilizing quantitative real-time polymerase chain reaction and western blotting. N-SNPs significantly reduced tumor size in mice without affecting body weight and did not compromise liver function or alter blood parameters. Besides, N-SNPs negatively impact membrane integrity and metabolic activity and significantly enhance oxidative stress by causing an imbalance in antioxidant activity in tumor tissues. Intriguingly, N-SNPs-stimulated apoptosis signaling pathways via a combination of enhanced and suppressed responses of pro- and antiapoptotic genes and proteins. The cytotoxic activity and apoptosis effect of N-SNPs in tumor tissue could be attributed to the surge in reactive oxygen species production and depletion of antioxidant activity. Certainly, N-SNPs could provide robust antitumor agents against solid tumors.